Innovation of Colorimetric Test Strips to Detect Paracetamol and Dexamethasone in Jamu Preparation - Angelina Bunga Rosari; Paramita Wahyu Septiani; Ischika Stefani; Odilia Dhea Christina (Duta Pharma Journal, 2026)
Background: The addition of chemical drugs to traditional herbal medicines (jamu) remains a public health concern because consumers may unknowingly be exposed to substances that can cause harmful effects. Paracetamol and dexamethasone are among the chemical drugs commonly misused in jamu products for pain, rheumatism, and gout. Objective: This study aimed to develop colorimetric test strips for the rapid qualitative detection of paracetamol and dexamethasone in jamu preparations. Methods: Laboratory experimental research was conducted using Whatman No. 4 filter paper as the test-strip medium. The paper was immobilized with 10% iron (III) chloride (FeCl?) for paracetamol detection and a reagent mixture of anhydrous acetic acid, concentrated sulfuric acid, and iodine for dexamethasone detection. Five jamu samples for aches, pain, and gout obtained from Pasar Kliwon, Temanggung, Central Java, were tested. Standard paracetamol and dexamethasone solutions served as positive controls, while distilled water was used as a negative control. Results: Paracetamol produced a yellowish-green color response with FeCl?, whereas dexamethasone produced a dark brown to reddish-brown color response with the reagent mixture. Four of the five tested jamu samples showed positive results for at least one chemical drug, while one sample was negative for both analytes. Conclusion: The developed colorimetric test strips have potential as a practical, rapid, and economical preliminary screening method for detecting paracetamol and dexamethasone in jamu. Further validation is required to assess selectivity, accuracy, precision, detection limit, and stability.